A conceptual model towards knowledge productivity behaviour - Dahari, Siti Nur Shahira; Abdul Rahman, Abd Latif; Mohamed Sawal, Mohd Zool Hilmie; Mohamad Tanuri, Zati Atiqah (2014)
This research investigates the aspects impacting the Knowledge Productivity Behavior among librarian by using five dimensions of Big Five Personality traits namely openness, conscientiousness, extraversion, agreeableness and neuroticism through attitude perspectives.In the context of twenty first century librarian, the shift in the librarian's role has change due to technological changes as well as a change in the instructional, and supporting universities government needs.Thus librarian not only providing services but also producing research and publications especially in Research Universities Library.These changes have brought about a new image for the librarian with the ability to produce new knowledge base and skill set. Hence library is not only a place that provide information but also producing information. Nevertheless the librarian acceptance of this new task is not very overwhelming as we havent explore what are the factors that may lead to this scenario; reluctant to produce publication or research.Very few have attempted to discover the role of Big Five Personality traits and Attitude on Knowledge Productivity Behavior among librarians.In particular, research concentrating on Malaysian librarians is still very limited. Thus in this research the Big Five Personality (BFP) will be used in order to investigate especially in the aspects of personality and attitude.